Improving the quality of learning through assignment system. (March 2019) - Delita, Fitra; Arif, Muhammad; Rosni,; Sitompuland Rohani, Marlinang
Abstract: Education sector must be able to produce graduates who have competitiveness in the workplace especially in the industrial era 4.0. This can be achieved through a learning process which integrates soft skills and hard skills. Assignments as part of the learning process need to be structured in order to balance these two abilities. The main objective of this research is to identify the design and development of 6 assignments and evaluate the application of 6 assignments in the Department of Geography Education. This research is an evaluation research using a qualitative approach. The subjects of this study were lecturers and students in Geography Education Department. Data were obtained through questionnaires which were given to lecturers and students as well as documentary studies. Furthermore, the data were analyzed descriptively using scores that converted into several categories. The results of the study showed: (1) the design and development of course assignments involved teaching teams who discussed about the form, systematics and assessment rubrics of tasks; (2) The results of the evaluation on the implementation of 6 tasks was all aspects included in "good" category but it still needs to improve in idea formulation.